2016
DOI: 10.1080/2000656x.2016.1237956
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of autologous platelet-rich plasma (PRP) after long-term storage at −20 °C without any preservation agent

Abstract: The growth factor levels on days 7 and 14 suggest that autologous PRP can be stored at -20 °C without preservative agents, although in vivo studies are required in order to evaluate the clinical efficacy of the detected growth factor levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 18 publications
1
21
0
3
Order By: Relevance
“…Similarly, Wen et al reported that the concentrations of VEGF, epidermal growth factor (EGF), FGF‐B, IGF‐1, and PDGF‐AA were not only sustained but also showed an increase after 7 days at a storage temperature of 22°C. However, Hosnuter et al found that the levels of EGF, VEGF, PDGF, IGF‐1, and TGF‐β1 were significantly decreased after 7 days in PRP stored at −20℃. In our study, with activation, the concentration of all growth factors (except for FGF‐B) were similar at each time point tested during 7 days of storage, regardless of storage temperature, with TGF‐β1 reaching its highest concentration on day 7.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, Wen et al reported that the concentrations of VEGF, epidermal growth factor (EGF), FGF‐B, IGF‐1, and PDGF‐AA were not only sustained but also showed an increase after 7 days at a storage temperature of 22°C. However, Hosnuter et al found that the levels of EGF, VEGF, PDGF, IGF‐1, and TGF‐β1 were significantly decreased after 7 days in PRP stored at −20℃. In our study, with activation, the concentration of all growth factors (except for FGF‐B) were similar at each time point tested during 7 days of storage, regardless of storage temperature, with TGF‐β1 reaching its highest concentration on day 7.…”
Section: Discussionmentioning
confidence: 98%
“…While earlier studies [14][15][16][25][26][27] have examined growth factor concentration, data on the effect of various storage conditions on the concentration of various growth factors in PRP are limited. In addition, none of these studies compared the effect of storage and activation on growth factor concentrations in PRP.…”
mentioning
confidence: 99%
“…Conditions affecting the quality and effects of PRP include: the age, sex, and pathophysiology of blood donors during PRP preparation; methods of drawing blood; anticoagulants; centrifugation time/speed/temperature; preservation method of PRP; interval and dose of use.…”
Section: Discussionmentioning
confidence: 99%
“…It also points to a fast and effective preparation protocol for patients with up to 189,000 platelets/mm 3 , with biological activity tested in vivo, aiming at the preparation of PRP. CHO, 2008;SERRANO et al, 2010;ROFFI et al, 2014;GERSCH et al, 2017;HOSNUTER et al, 2017;MOORE et al, 2017). Diferenças estatísticas foram consideradas quando p < 0.05.…”
Section: Agradecimentosmentioning
confidence: 99%
“…O PRP é obtido a partir de uma amostra de sangue venoso autólogo anticoagulada passando por um processo de centrifugação que pode envolver uma ou mais centrifugações para selecionar uma fração plasmática contendo uma maior concentração de plaquetas e menor seleção de eritrócitos (WEHLING et al, 2017). Há diferentes formas para a obtenção do PRP, e o concentrado de plaquetas pode ser classificado em PRP puro (P-PRP), eliminando os leucócitos no isolamento ou em PRP com alta concentração de leucócitos (L-PRP), o qual possui alta concentração de leucócitos (DOHAN EHRENFEST; RASMUSSON; ALBREKTSSON, 2009).O PRP pode ser preparado para armazenamento sob diversas formas como congelamento, criopreservação ou liofilização, podendo ter ou não adicionamento de solução de estabilização(GERSCH et al, 2017;HOSNUTER et al, 2017;PIETRAMAGGIORI et al, 2006;ROFFI et al;2014;CHO, 2008;SERRANO et al;2009;MOORE et al;.…”
unclassified